Business Administration and Business Economics: Array - Collective Authors (Acta Universitatis Danubius. Œconomica, 2021)
This study tests Wagner’s law in Nigeria in both the short and long-run using the autoregressive distributed lag (ARDL) technique of estimation and controlling for structural breaks between the periods 1981-2016. Results showed that both in the short and long-run, evidence pointed to a negative but insignificant relationship between government expenditure and economic growth, with a larger negative effect in the long-run. The study controlled for oil export earnings, which was found to positively and significantly influence government spending in both the short and long-run. Results did not support the Wagner law. It was therefore recommended that the economy be diversified into more labour intensive sectors so as to increase output and income per capita and so that government expenditure can be based more on tax receipts than on oil export earnings as more financially responsible households will demand increase in government expenditure as their level of income increases, especially for the provision of public sector services the households currently bear.